Penerbitan Kartu Keluarga: Tinjauan Kemaslahatan Terhadap Legitimasi Status Perkawinan Bagi Pasangan Nikah Siri - Fauzan; Rohmadi (Al-Ulum, 2023)
This study aims to comprehensively describe the issuance of Family Cards in the perspective of maslahah (social benefit) and justice for the legitimacy of marriage for sirri married couples in Bengkulu Province. This research is a qualitative empirical research with a statutory approach, a case and field approach, and a concept approach. This study found that the issuance of Family Cards for marriages of unmarried couples is a form of upholding justice in a social (commutative) framework where everyone has the same rights over marital status. On the other hand, the issuance of a Family Card for unmarried couples can be categorized as maslahah al-khassah (special benefit) which benefits only a few parties, not maslahah al-ammah (general benefit) which applies to the whole community. This study also found that the impact of including the statement "Unregistered Marriage" in the issuance of Family Cards for unregistered married couples can lead to maslahah al-mulghah in the form of legal confusion regarding the legality of one's marriage while at the same time hindering the updating of centralized data which is on the government's agenda.